(untitled) (Scientific journal of the Fergana State University, 2024)
Lakes, which are common in different altitude zones of mountainous regions, are one of the main sources of flood risk. In particular, a special place in this regard is occupied by such types as dam, glacial, moraine, landslide and snow avalanche. All of them together can be classified as “dam lakes”. Dammed lakes sometimes cause catastrophic floods due to the failure of their dams for various reasons, causing great damage to people’s homes and property. In this regard, their study, prevention of the risk of floods that can arise for various reasons, their forecasting and assessment of the level of danger are some of the important tasks facing limnologists today. The main objective of this study is to assess the flood risk of dammed lakes based on their genetic classification. The studies used methods of hydrometeorological analysis and geographic similarity.